Self-assembled peptide-substance P hydrogels alleviate inflammation and ameliorate the cartilage regeneration in knee osteoarthritis - Kim, Sang Jun; Kim, Ji Eun; Choe, Goeun; Song, Da Hyun; Kim, Sun Jeong; Kim, Tae Hee; 류진; Kim, Soo Hyun; Jung, Youngmee (The Korean Society for Biomaterials | BioMed Central, 2023)
Background Self-assembled peptide (SAP)-substance P (SP) hydrogels can be retained in the joint cavity longer than SP alone, and they can alleviate inflammation and ameliorate cartilage regeneration in knee osteoarthritis (OA). We conducted a preclinical study using diverse animal models of OA and an in vitro study using human synoviocytes and patient-derived synovial fluids to demonstrate the effect of SAP-SP complex on the inflammation and cartilage regeneration. Methods Surgical induction OA model was prepared with New Zealand white female rabbits and chemical induction, and naturally occurring OA models were prepared using Dunkin Hartely female guinea pigs. The SAP-SP complex or control (SAP, SP, or saline) was injected into the joint cavities in each model. We performed microcomputed tomography (Micro-CT) analysis, histological evaluation, immunofluorescent analysis, and terminal deoxynucleotidyl transferase deoxyuridine triphosphate nick-end labeling (TUNEL) assay and analyzed the recruitment of intrinsic mesenchymal stem cells (MSCs), macrophage activity, and inflammatory cytokine in each OA model. Human synoviocytes were cultured in synovial fluid extracted from human OA knee joints injected with SAP-SP complexes or other controls. Proliferative capacity and inflammatory cytokine levels were analyzed. Results Alleviation of inflammation, inhibition of apoptosis, and enhancement of intrinsic MSCs have been established in the SAP-SP group in diverse animal models. Furthermore, the inflammatory effects on human samples were examined in synoviocytes and synovial fluid from patients with OA. In this study, we observed that SAP-SP showed anti-inflammatory action in OA conditions and increased cartilage regeneration by recruiting intrinsic MSCs, inhibiting progression of OA. Conclusions These therapeutic effects have been validated in diverse OA models, including rabbits, Dunkin Hartley guinea pigs, and human synoviocytes. Therefore, we propose that SAP-SP may be an effective injectable therapeutic agent for treating OA. [GRAPHICS]